A super-hydrophobic composite fabric with micro-nano surface structure and preparation method thereof
By constructing the micro-nano surface structure of Al3+ fatty acid calcium/calcium carbonate nanoparticles and cellulose electrospun films on natural fiber materials, and performing complexing of catechin and fatty amines, it is solved that it is difficult for natural fiber materials to achieve super-extension. The problem of hydrophobic effect has achieved a significant improvement in the superhydrophobic performance of the fabric.
Patent Information
- Application Number
- CN202410534191.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The prior art is difficult to simply and effectively construct micro-nano multi-stage composite structures on natural fiber materials to achieve superhydrophobic effects.
By adding Al3+ fatty acid calcium/calcium carbonate nanoparticles to the cellulose solution, an electrospinning method is used to prepare a cellulose electrospinning film, and the complexing treatment of catechin and fatty amine on the film will be carried out, and the final modification will be made. The electrospinning film is combined with the fabric and coated with aqueous sodium hydroxide solution to form a superhydrophobic fabric.
The micro-nano surface structure of the fabric surface structure is realized, which significantly improves the superhydrophobic properties of the fabric and has good anti-fouling and oil-water separation capabilities.
Smart Images

Figure BDA0004818997180000091 
Figure BDA0004818997180000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional fabrics, and in particular to a super-hydrophobic composite fabric with a micro-nano surface structure and a preparation method thereof. Background Art
[0002] Superhydrophobicity is closely related to the textile industry. Scientists have tried a lot of methods to give fabrics superhydrophobic properties. For example, the use of dip coating to hydrophobically modify cotton fabrics to make them superhydrophobic (contact angle>150°) can improve the anti-fouling ability of cotton fabrics and achieve efficient oil-water separation. Using the spray method to treat one side of the fabric hydrophilically and the other side hydrophobically can make a moisture-absorbing and quick-drying sports fabric. Therefore, it is feasible and extremely beneficial to modify the fabric to be superhydrophobic.
[0003] The superhydrophobic property of a solid surface is determined by both the surface free energy and the roughness of the solid surface. A superhydrophobic surface can be achieved in two ways: 1) constructing a micro-nano multi-level composite structure on the solid surface to increase the surface roughness; 2) modifying the solid surface with a micro-nano multi-level composite structure with a low surface energy substance to reduce the surface energy of the material. At present, the methods for constructing a micro-nano multi-level composite structure on a solid surface include: sol-gel method, plasma method, electrospinning method, physical or chemical vapor deposition method, template method, electrochemical method, and phase separation method. In recent years, many researchers have used the above methods to construct rough surfaces on different substrates (such as glass, silicon wafers, and metals) and achieved superhydrophobic effects. However, the above methods have certain limitations in the application of natural fiber materials (such as cotton, linen, silk, and wool), which is mainly due to the poor chemical resistance and physical and mechanical properties of natural fiber materials. How to simply and effectively construct a micro-nano multi-level composite structure on the surface of a fabric to achieve a superhydrophobic effect on the fabric has become a research hotspot in the field of fabric finishing. Summary of the invention
[0004] Technical problem to be solved: The purpose of the present invention is to provide a super-hydrophobic composite fabric with a micro-nano surface structure and a preparation method thereof, and to construct a micro-nano multi-level composite structure on the surface of the fabric so that the fabric has a super-hydrophobic effect.
[0005] Technical solution: A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure, comprising the following steps:
[0006] S1. adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a cellulose solution;
[0007] S2. Load Al 3+Adding fatty acid calcium / calcium carbonate nanoparticles to the cellulose solution prepared in step S1, stirring and mixing to obtain a cellulose electrospinning solution, and electrospinning the spinning solution to obtain a cellulose electrospinning membrane;
[0008] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, taking it out and allowing the acetone to evaporate naturally to obtain a catechin-complexed cellulose electrospun membrane;
[0009] S4. adding the catechin-complexed cellulose electrospinning membrane prepared in step S3 to an ether solution containing a fatty amine, taking it out and allowing the ether to volatilize to obtain a modified electrospinning membrane;
[0010] S5. Compounding the modified electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0011] S6. Coat the surface of one side of the composite fabric having the modified electrospinning membrane with a sodium hydroxide aqueous solution and dry it naturally to obtain a superhydrophobic fabric.
[0012] Preferably, the concentration of the cellulose solution in step S1 is 1.5-2.5 wt %.
[0013] Preferably, in step S2, Al 3+ The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps:
[0014] S11. Mixing equal volumes of calcium chloride and sodium dodecyl sulfate, then adding a mixed solution of sodium fatty acid and sodium carbonate, stirring rapidly, separating the precipitate, washing and drying to obtain calcium fatty acid / calcium carbonate nanoparticles;
[0015] S12. Add fatty acid calcium / calcium carbonate nanoparticles to the aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
[0016] Preferably, in step S2, Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.1-0.5wt%. The thickness of the cellulose electrostatic spinning membrane is 0.1-0.5mm, and the porosity is 45-65%.
[0017] Preferably, in step S3, the content of catechins in acetone is 2.5-4.5 wt %, and the immersion time of the cellulose electrospinning membrane in the acetone solution containing catechins is 30-90 min.
[0018] Preferably, the fatty amine in step S4 comprises any one of dodecylamine, ethylenediamine, octanediamine or octadecylamine, the content of the fatty amine in diethyl ether is 2-5wt%, and the catechin-complexed cellulose electrospinning membrane is immersed in the diethyl ether solution for 10-60min.
[0019] Preferably, the concentration of the sodium hydroxide aqueous solution in step S6 is 0.01-0.05 mol / L, and the coating amount is 8-15 g / m 2 Preferably, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate in step S11 is 2:1:0.5-1:1-2. Preferably, the concentration of aluminum chloride solution in step S12 is 0.05-0.2 mol / L.
[0020] Any of the above preparation methods can prepare a super-hydrophobic composite fabric with a micro-nano surface structure.
[0021] Beneficial effects: The super-hydrophobic composite fabric with micro-nano surface structure of the present invention has the following advantages:
[0022] 1. In the present invention, the surface of the fabric is composited with an electrospinning membrane having a micro-nano surface structure, so that the fabric has a micro-nano surface structure, thereby obtaining a super-hydrophobic effect;
[0023] 2. First, in the present invention, nanostructured fatty acid calcium / calcium carbonate particles are prepared, and the nanoparticles can be added to the electrospinning solution. The prepared spinning membrane has nanoparticles, and the electrospun fibers are stacked by micron or nanofibers. The electrospun fibers themselves have a micron structure, and different porosities trap different amounts of air in the electrospinning membrane. Appropriate air trapping can achieve different hydrophobic effects, so the obtained electrospinning membrane has a micro-nano composite structure; 3. Secondly, sodium fatty acid is added to the mixed solution, and sodium fatty acid can react with calcium chloride to generate calcium fatty acid, so that the surface of the prepared nanoparticles has hydrophobic groups, further improving the hydrophobic properties of the fabric;
[0024] 4. Third, cellulose itself has more hydrophilic groups. The cellulose electrospun membrane is added to the acetone solution of catechins for impregnation. 3+ It can form a complex with the phenolic hydroxyl group in catechins, but Al 3+The phenolic hydroxyl groups in catechins cannot be completely complexed, and the catechin-complexed cellulose electrospun membrane is then immersed in a solution containing fatty amines. The remaining phenolic hydroxyl groups combine with the fatty amines to generate long fatty chains on the surface of the electrospun membrane, further improving the hydrophobic properties; 5. Finally, a sodium hydroxide aqueous solution is coated on one side of the composite fabric with the modified electrospun membrane. After the electrospun membrane is coated with alkali solution, the membrane will shrink to a certain extent, so that the membrane surface has a more significant micro-nano structure, further improving the hydrophobic effect of the fabric. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:
[0026] Example 1
[0027] Al 3+ The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps:
[0028] S11. Calcium chloride and sodium dodecyl sulfate were mixed in equal volumes, and then a mixed solution of sodium fatty acid and sodium carbonate was added, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate being 2:1:0.5:1.5, and the mixture was stirred rapidly, the precipitate was separated, washed and dried to obtain calcium fatty acid / calcium carbonate nanoparticles;
[0029] S12. Add fatty acid calcium / calcium carbonate nanoparticles to a 0.05 mol / L aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
[0030] Example 2
[0031] Al 3+ The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps:
[0032] S11. Calcium chloride and sodium dodecyl sulfate were mixed in equal volumes, and then a mixed solution of sodium fatty acid and sodium carbonate was added, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate being 2:1:0.8:1.6, and the mixture was stirred rapidly, the precipitate was separated, washed and dried to obtain calcium fatty acid / calcium carbonate nanoparticles;
[0033] S12. Add fatty acid calcium / calcium carbonate nanoparticles to a 0.2 mol / L aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
[0034] Example 3
[0035] Al 3+The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps:
[0036] S11. Calcium chloride and sodium dodecyl sulfate were mixed in equal volumes, and then a mixed solution of sodium fatty acid and sodium carbonate was added, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate being 2:1:0.6:1.5, and the mixture was stirred rapidly, the precipitate was separated, washed and dried to obtain calcium fatty acid / calcium carbonate nanoparticles;
[0037] S12. Add fatty acid calcium / calcium carbonate nanoparticles to a 0.08 mol / L aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
[0038] Example 4
[0039] Al 3+ The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps:
[0040] S11. Calcium chloride and sodium dodecyl sulfate were mixed in equal volumes, and then a mixed solution of sodium fatty acid and sodium carbonate was added, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate being 2:1:0.7:1.5, and the mixture was stirred rapidly, the precipitate was separated, washed and dried to obtain calcium fatty acid / calcium carbonate nanoparticles;
[0041] S12. Add fatty acid calcium / calcium carbonate nanoparticles to a 0.0.15 mol / L aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
[0042] Measurement Example 1-4 Preparation of Al-loaded 3+ The particle size of fatty acid calcium / calcium carbonate nanoparticles is shown in Table 1 below:
[0043] Particle size / nm Example 1 236 Example 2 198 Example 3 257 Example 4 204
[0044] Example 5
[0045] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0046] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 1.5 wt % cellulose solution;
[0047] S2. Prepared in Example 1 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.1wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.2mm and the porosity is 55.6%.
[0048] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 2.5 wt %, and the immersion time is 90 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0049] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing octanediamine, wherein the content of octanediamine in the ether is 2 wt %, and the immersion time is 60 min. After the ether is volatilized, a modified electrospun membrane is obtained;
[0050] S5. Compounding the modified electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0051] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.01 mol / L, and the coating amount is 8 g / m 2 , dry naturally to obtain super hydrophobic fabric.
[0052] Example 6
[0053] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0054] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2.5 wt% cellulose solution;
[0055] S2. Prepared in Example 2 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.5wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.15mm and the porosity is 48.9%.
[0056] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 4.5 wt %, and the immersion time is 30 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0057] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing dodecylamine, wherein the content of octanediamine in the ether is 5 wt %, and the immersion time is 10 min. After the ether is volatilized, a modified electrospun membrane is obtained;
[0058] S5. Compounding the modified electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0059] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.05 mol / L, and the coating amount is 15 g / m 2 , dry naturally to obtain super hydrophobic fabric.
[0060] Example 7
[0061] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0062] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 1.8 wt % cellulose solution;
[0063] S2. Prepared in Example 3 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.2wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.18mm and the porosity is 60.8%.
[0064] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 3.2 wt %, and the immersion time is 80 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0065] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing octanediamine, wherein the content of octanediamine in ether is 2.8 wt %, and the immersion time is 20 min. After being taken out, the ether is volatilized to obtain a modified electrospun membrane; S5. The modified electrospun membrane is compounded with a fabric through an adhesive to obtain a composite fabric;
[0066] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.04 mol / L, and the coating amount is 14 g / m 2 , dry naturally to obtain super hydrophobic fabric.
[0067] Example 8
[0068] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0069] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2.2 wt % cellulose solution;
[0070] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.4wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.16mm and the porosity is 50.9%.
[0071] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 4 wt %, and the immersion time is 45 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0072] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing ethylenediamine, wherein the content of octanediamine in the ether is 4 wt %, and the immersion time is 40 min. After the ether is volatilized, a modified electrospun membrane is obtained;
[0073] S5. Compounding the modified electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0074] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.02 mol / L, and the coating amount is 10 g / m 2 , dry naturally to obtain super hydrophobic fabric.
[0075] Example 9
[0076] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0077] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2 wt % cellulose solution;
[0078] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.32wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.19mm and the porosity is 52.8%.
[0079] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 3.5 wt %, and the immersion time is 60 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0080] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing octadecylamine, wherein the content of octanediamine in the ether is 3.5 wt %, and the immersion time is 30 min. After the ether is taken out, the modified electrospun membrane is obtained until the ether evaporates, and S5. The modified electrospun membrane is compounded with the fabric through an adhesive to obtain a composite fabric;
[0081] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.03 mol / L, and the coating amount is 12 g / m 2 , dry naturally to obtain super hydrophobic fabric.
[0082] Comparative Example 1
[0083] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0084] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2.2 wt % cellulose solution;
[0085] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.32wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.18mm and the porosity is 55.6%.
[0086] S3. Compounding the cellulose electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0087] S4. Coat the surface of one side of the composite fabric with the cellulose electrospun membrane with a sodium hydroxide aqueous solution having a concentration of 0.03 mol / L, and the coating amount is 12 g / m 2 , dry naturally to get hydrophobic fabric.
[0088] Comparative Example 2
[0089] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0090] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2.5 wt% cellulose solution;
[0091] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.5wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.16mm and the porosity is 50.6%.
[0092] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 4.5 wt %, and the immersion time is 30 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0093] S4. Compounding the catechin-complexed cellulose electrospun membrane with fabrics through an adhesive to obtain a composite fabric;
[0094] S5. Coat the surface of the composite fabric with the electrospun membrane on one side with a sodium hydroxide aqueous solution having a concentration of 0.01 mol / L, and the coating amount is 10 g / m 2 , dry naturally to get hydrophobic fabric.
[0095] Comparative Example 3
[0096] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0097] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 1.8 wt % cellulose solution;
[0098] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.2wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.18mm and the porosity is 54.6%.
[0099] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 3 wt %, and the immersion time is 80 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0100] S4. Add the catechin-complexed cellulose electrospun membrane prepared in step S3 to an ether solution containing octanediamine, wherein the content of octanediamine in the ether is 2.8 wt %. The immersion time is 20 min. After taking it out, wait until the ether evaporates to obtain a modified electrospun membrane. S5. Compound the modified electrospun membrane with the fabric through an adhesive to obtain a hydrophobic fabric.
[0101] Comparative Example 4
[0102] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0103] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2.5 wt% cellulose solution;
[0104] S2. Load Al 3+ Nano calcium carbonate particles are added to the cellulose solution prepared in step S1 to carry Al 3+ The concentration of nano calcium carbonate particles in the cellulose solution is 0.5wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.17mm and the porosity is 49.6%.
[0105] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 4 wt %, and the immersion time is 60 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0106] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing dodecylamine, wherein the content of octanediamine in the ether is 5 wt %, and the immersion time is 10 min. After the ether is volatilized, a modified electrospun membrane is obtained;
[0107] S5. Compounding the modified electrospun membrane with fabric through an adhesive to obtain a composite fabric;
[0108] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.05 mol / L, and the coating amount is 10 g / m 2 , dry naturally to obtain a hydrophobic fabric;
[0109] Among them, Al 3+ The nano calcium carbonate particles are prepared by immersing nano porous calcium carbonate in an aluminum chloride solution and then filtering and drying the solution.
[0110] Comparative Example 5
[0111] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0112] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 2 wt % cellulose solution;
[0113] S2. Prepared in Example 4 Al 3+ Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.32wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.19mm and the porosity is 92.6%.
[0114] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 3.5 wt %, and the immersion time is 60 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0115] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing octadecylamine, wherein the content of octanediamine in the ether is 3.4 wt %, and the immersion time is 30 min. After the ether is volatilized, a modified electrospun membrane is obtained. S5. The modified electrospun membrane is compounded with a fabric through an adhesive to obtain a composite fabric.
[0116] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.05 mol / L, and the coating amount is 14 g / m 2 , dry naturally to get hydrophobic fabric.
[0117] Comparative Example 6
[0118] A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure comprises the following steps:
[0119] S1. Adding delipidated cellulose to a DMAc / LiCl mixed solvent to dissolve the cellulose to obtain a 1.8 wt % cellulose solution;
[0120] S2. Prepared in Example 4 Al 3+Fatty acid calcium / calcium carbonate nanoparticles are added to the cellulose solution prepared in step S1 to load Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.35wt%, and the mixture is stirred and mixed to obtain a cellulose electrospinning solution. The spinning solution is electrospun by electrospinning to obtain a cellulose electrospinning membrane. The thickness of the cellulose electrospinning membrane is 0.25mm and the porosity is 33.6%.
[0121] S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, wherein the content of catechins in acetone is 3.2 wt %, and the immersion time is 60 min. After taking out, the acetone is naturally volatilized to obtain a catechin-complexed cellulose electrospun membrane;
[0122] S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing octadecylamine, wherein the content of octanediamine in the ether is 3.0 wt %, and the immersion time is 30 min. After the ether is taken out, the modified electrospun membrane is obtained until the ether evaporates; S5. The modified electrospun membrane is compounded with the fabric through an adhesive to obtain a composite fabric;
[0123] S6. Coat the surface of one side of the composite fabric with the modified electrospinning membrane with a sodium hydroxide aqueous solution having a concentration of 0.05 mol / L, and the coating amount is 13 g / m 2 , dry naturally to get hydrophobic fabric.
[0124] The hydrophobic properties of Examples 5-9 and Comparative Examples 1-6 were tested (the fabric layers in the above Examples and Comparative Examples were all polyester fabrics with the same warp and weft density):
[0125] Test 1: Static contact angle test between fabric and water:
[0126] Use a video contact angle meter to test the static water contact angle. The water volume is 6 μL each time. The reading is taken after the water drop contacts the fabric for 60 seconds. Measure 5 times at different locations on the same sample and take the average value.
[0127] Test 2: Friction resistance test of fabrics:
[0128] The super-hydrophobic fabric was tested using a friction color fastness tester. First, the fabric was cut into 20cm×10cm samples and fixed on the base of the friction color fastness tester. The parameters of the friction color fastness tester are 10 cycles; the movement speed of the friction head is 104mm / min; and the friction distance of each cycle is 208mm.
[0129]
[0130]
[0131] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a super-hydrophobic composite fabric with a micro-nano surface structure, characterized in that: The following steps are involved: S1. The delipidated cellulose was added to a DMAc / LiCl mixed solvent to dissolve the cellulose solution; S2. Load Al 3+ Adding fatty acid calcium / calcium carbonate nanoparticles to the cellulose solution prepared in step S1, stirring and mixing to obtain a cellulose electrospinning solution, and electrospinning the spinning solution to obtain a cellulose electrospinning membrane; S3. adding the cellulose electrospun membrane prepared in step S2 to an acetone solution containing catechins, and then taking it out to allow the acetone to evaporate naturally to obtain a catechin-complexed cellulose electrospun membrane; S4. The catechin-complexed cellulose electrospun membrane prepared in step S3 is added to an ether solution containing a fatty amine, and then taken out to volatilize the ether to obtain a modified electrospun membrane; S5. Compounding the modified electrospun membrane with a fabric through an adhesive to obtain a composite fabric; S6. The composite fabric having one side of the modified electrospinning membrane is coated with an aqueous sodium hydroxide solution and allowed to dry naturally to obtain a super-hydrophobic fabric; Wherein, in step S2, Al 3+ The preparation of fatty acid calcium / calcium carbonate nanoparticles comprises the following steps: S11. Mixing equal volumes of calcium chloride and sodium dodecyl sulfate, then adding a mixed solution of sodium fatty acid and sodium carbonate, stirring rapidly, separating the precipitate, washing and drying to obtain calcium fatty acid / calcium carbonate nanoparticles; S12. Add fatty acid calcium / calcium carbonate nanoparticles to the aluminum chloride solution and stir until completely adsorbed to obtain Al-loaded 3+ Fatty acid calcium / calcium carbonate nanoparticles.
2. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: The concentration of the cellulose solution in step S1 is 1.5-2.5 wt %.
3. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: In step S2, Al 3+ The concentration of fatty acid calcium / calcium carbonate nanoparticles in the cellulose solution is 0.1-0.5wt%.
4. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: In the step S3, the content of catechins in acetone is 2.5-4.5 wt %, and the immersion time of the cellulose electrospinning membrane in the acetone solution containing catechins is 30-90 min.
5. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: In step S4, the fatty amine includes any one of dodecylamine, ethylenediamine, octanediamine or octadecylamine, the content of the fatty amine in diethyl ether is 2-5wt%, and the catechin-complexed cellulose electrospinning membrane is immersed in the diethyl ether solution for 10-60 minutes.
6. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution in step S6 is 0.01-0.05 mol / L, and the coating amount is 8-15 g / m 2 .
7. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: In step S11, the molar ratio of calcium chloride, sodium dodecyl sulfate, sodium fatty acid and sodium carbonate is 2:1:0.5-1:1-2.
8. The method for preparing the super-hydrophobic composite fabric with micro-nano surface structure according to claim 1, characterized in that: The concentration of the aluminum chloride solution in step S12 is 0.05-0.2 mol / L.
9. A super-hydrophobic composite fabric with a micro-nano surface structure is prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of nano bamboo fiber composite material
CN103173892A
PH responsive microcapsule type protein vaccine vector and preparation method thereof
CN105214100A